Implementasi Rencana Program Pembelajaran Berbasis Kompetensi Pada Pembelajaran Kompetensi Dasar Menulis Program CNC - Yayat, Yayat (INVOTEC, 2010)
This research aimed  to analyze and describe the mastery of the vocational high school student’s to basic competencies in writing CNC programs through the implementation of competence-based lesson plans,  with the cognitive aspect at understanding level, the psychomotor aspect  at guided instruction level, and affective aspect at responding level. The number of samples in this study are 33 students. Research carried out by using the method of quasi experiment research The data was analyzed using means, deviation standard,  percentage, and Normalized N-gain. The results showed that the mastery of the vocational high school student’s for basic competencies in writing CNC programs through the implementation of competence-based lesson plans classified as enough category. As for every aspect for cognitive, psychomotor, and  affective aspects are also classified into medium category.